Surgical Interventions for Supratentorial Intracranial Hemorrhage: The Past, Present, and Future - Patel, Smruti K.; Saleh, Mohamed S.; Body, Alaina; Zuccarello, Mario (Seminars in Neurology, 2021)
Spontaneous supratentorial intracranial hemorrhage is extremely disabling and is associated with high mortality. Primary treatment for patients with this disease process is maximal medical management with blood pressure control and correction of clotting disorders due to comorbid conditions or medications. Over the past decade, significant strides have been made in understanding the benefits of surgical intervention in the treatment of intracranial hemorrhage through multiple clinical trials. In this article, we review the evolution of surgical treatments beginning with the STICH trials, discuss new developments with minimally invasive surgical strategies, and provide a brief update regarding ongoing trials and future directions in the treatment of spontaneous supratentorial intracranial hemorrhage.
Keywords: intracranial hemorrhage; hemorrhagic stroke; surgical intervention; STICH; MISTIE